Политико- правовой анализ «Трехстороннего заявления о прекращении огня в Нагорном Карабахе» 10 ноября 2020 года - Марукян, Армен (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The «trilateral statement» signed in gross violation of a number of basic principles and norms of international treaty law, which, in terms of its content and the issues under discussion, as well as from the legal point of view, is not a statement on a ceasefire, but an international treaty attempting to resolve the Karabakh conflict. The signing of this illegal document is only a temporary, situational solution to the issue, which does not settle the conflict, but only freezes it, because the concessions made to both Azerbaijan and Turkey not only do not weaken, but, on the contrary, whet the appetite of this anti-Armenian genocidal bloc. Armenians in Armenia, Artsakh, and around the world consider the "trilateral statement" to be simply a documented post-war reality, but never a legal document that finally settles the Karabakh issue. The Armenian people will never accept such injustice, illegality, will fight by all possible means to restore their violated rights, which will eventually lead to a comprehensive, complete settlement of the Karabakh conflict and establish long-term security and peace in the region.
Keywords: История